2012
DOI: 10.1111/j.1708-8305.2012.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Illness Symptoms at High Altitude and Their Relationship With Acute Mountain Sickness: A Prospective Cohort Study

Abstract: Upper respiratory symptoms and anxiety increasingly contributed to symptom burden as altitude was gained. Data were consistent with increased heart rate, decreased arterial oxygen saturation, reduced fluid intake, and upper respiratory symptoms being causally associated with AMS. Upper respiratory symptoms and fluid intake are the simplest targets for intervention to reduce AMS during high altitude exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…Thus, future studies should implement a more robust sleep questionnaire, for example, the Groningen Sleep Questionnaire and/or direct polysomnography assessments. Third, due to the relatively small numbers of questionnaire items, the effect of other potential candidate factors, such as a history of previous AMS, migraine (Richalet et al, 2012;Canouï-Poitrine et al, 2014;Vinnikov et al, 2014), body mass index (obesity) (Beidleman et al, 2013), physical activity level (Beidleman et al, 2013), physical exertion (Roach et al, 2000), current smoking status (Beidleman et al, 2013;Vinnikov et al, 2014), cardiorespiratory responses to hypoxia (Oliver et al, 2012;Richalet et al, 2012;Canouï-Poitrine et al, 2014), and hydration status, including drinking habits (Mairer et al, 2009;Oliver et al, 2012), which have been investigated previously, on AMS in this population remains uncertain. Although future studies that include these items are warranted, our results clearly demonstrated that sleeping altitude may play an important role in increasing the prevalence and severity of AMS.…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, future studies should implement a more robust sleep questionnaire, for example, the Groningen Sleep Questionnaire and/or direct polysomnography assessments. Third, due to the relatively small numbers of questionnaire items, the effect of other potential candidate factors, such as a history of previous AMS, migraine (Richalet et al, 2012;Canouï-Poitrine et al, 2014;Vinnikov et al, 2014), body mass index (obesity) (Beidleman et al, 2013), physical activity level (Beidleman et al, 2013), physical exertion (Roach et al, 2000), current smoking status (Beidleman et al, 2013;Vinnikov et al, 2014), cardiorespiratory responses to hypoxia (Oliver et al, 2012;Richalet et al, 2012;Canouï-Poitrine et al, 2014), and hydration status, including drinking habits (Mairer et al, 2009;Oliver et al, 2012), which have been investigated previously, on AMS in this population remains uncertain. Although future studies that include these items are warranted, our results clearly demonstrated that sleeping altitude may play an important role in increasing the prevalence and severity of AMS.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies have shown that maladjustment of multiple factors, including respiration, gas exchange, and fluid balance, can lead to AMS [5]. However, the exact etiology and pathogenesis of AMS are not yet entirely clear, and susceptibility to AMS is markedly variable among individuals [6,7]. As a result, clinicians still cannot effectively predict susceptibility to AMS.…”
Section: Introductionmentioning
confidence: 99%
“…19 Therefore, the recommendation to increase fluid intake could possibly be one of the simplest interventions to reduce symptoms of altitude illness, as was recently concluded by Gatterer and colleagues and others. [20][21][22] On the other hand, it might be that dark urine merely is a consequence and not a risk factor of altitude illness.…”
Section: Predictorsmentioning
confidence: 95%